Expression of angiogenesis‐related gene profiles and development of resistance to tyrosine‐kinase inhibitor in advanced renal cell carcinoma: Characterization of sorafenib‐resistant cells derived from a cutaneous metastasis. (4th February 2013) - Karashima, Takashi; Fukuhara, Hideo; Tamura, Kenji; Ashida, Shingo; Kamada, Masayuki; Inoue, Keiji; Taguchi, Takahiro; Kuroda, Naoto; Shuin, Taro
Abstract : Objectives: To investigate the potential mechanism of development of resistance to tyrosine kinase inhibitor in renal cell carcinoma. Methods: A primary culture of renal cell carcinoma cells (KMRM‐S2) was established from an advanced renal cell carcinoma patient with cutaneous metastasis, who had not responded to sorafenib. A total of 84 human angiogenesis‐related genes were compared between cutaneous metastasis and the primary tumor by real time polymerase chain reaction. Spectral karyotyping and cell proliferation assay were carried out to determine the biological features of the cells. Results: Primary tumor was histopathologically diagnosed as high‐grade clear cell carcinoma with sarcomatoid change and rhabdoid features. The cutaneous metastasis also consisted of sarcomatoid components. Expression levels of many angiogenesis‐related genes in the cutaneous metastasis were relatively higher than those of primary tumor. Chromosomal analysis of the KMRM‐S2 showed cytogenetic abnormalities with hypertriploidy and translocation. In vitro proliferation assay showed the relatively higher resistance of KMRM‐S2 against sorafenib. Conclusions: The sarcomatoid change and rhabdoid features of renal cell carcinoma with cytogenetic hyperploidy might be associated with elevated expression of angiogenesis‐related genes, which leads to resistance against tyrosine kinase inhibitor. The present study might contribute to discovering novel therapeutic targets for the treatment of patients with advanced renal cell carcinoma resistant to tyrosine kinase inhibitor.